Relation of maternal prepregnancy body mass index with offspring bone mass in childhood: is there evidence for an intrauterine effect?(1)(2)(3)(4) - Macdonald-Wallis, Corrie (American Society for Nutrition, 2010)
Background: Evidence indicates that intrauterine skeletal development has implications for bone mass in later life and that maternal fat stores in pregnancy are important for fetal bone mineral accrual. Objective: We investigated whether childhood bone mass is influenced by maternal body mass index (BMI) via an intrauterine mechanism by comparing parental associations. Design: We conducted a multivariable regression analysis of 7121 children in the Avon Longitudinal Study of Parents and Children. Total body less head (TBLH) and spine bone measures were derived from dual-energy X-ray absorptiometry scans at a mean age of 9.9 y. Maternal and paternal BMI values were derived from self-reported weight and height during pregnancy. Results: Maternal prepregnancy BMI (SD score) was positively associated with offspring TBLH bone mineral content and bone mineral density (SD scores) [mean difference (95% CI): boys, 0.19 (0.16, 0.23) and 0.15 (0.12, 0.19), respectively; girls, 0.23 (0.19, 0.26) and 0.19 (0.16, 0.23), respectively] and spine bone mineral content and bone mineral density [boys, 0.20 (0.16, 0.24) and 0.18 (0.14, 0.22), respectively; girls, 0.22 (0.18, 0.26) and 0.21 (0.17, 0.25), respectively] and with TBLH and spine bone area–and spine area–adjusted bone mineral content. Associations of paternal BMI with these outcomes were similar, with no statistical evidence of a difference between maternal and paternal effects. Maternal associations were partly explained by offspring birth weight and gestational age and attenuated to the null after adjustment for offspring height and weight. Conclusion: The positive relation between maternal prepregnancy BMI and offspring bone mass is likely due to shared familial, genetic, and environmental characteristics rather than to an intrauterine mechanism.